Understanding Mental Well-Being Among University Students in Indonesia: A Descriptive Quantitative Analysis - Anandha Putri Rahimsyah; Muhammad Muhajirin; Nizza Nadya Rachmani; Khairul Bariyyah; Gian Sugiana Sugara; Tasya Aprilya; Nuraini Latifa Zulfa (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: Mental well-being is a crucial component of university students’ academic functioning and personal development. However, empirical evidence describing students’ mental well-being levels, particularly in non-Western contexts, remains limited. This study aims to describe the level of mental well-being among university students at two higher education institutions in Indonesia. Methodology: This study employed a descriptive quantitative design. A total of 449 undergraduate students were selected using proportionate stratified random sampling from two universities with different student population characteristics. Data were collected using the Indonesian-adapted version of the Warwick–Edinburgh Mental Well-Being Scale (WEMWBS). Descriptive statistical analysis was conducted to examine the distribution of students’ mental well-being levels. Main Findings: These findings highlight the importance of strengthening preventive and promotive mental health initiatives in higher education settings. Campus-based interventions, such as mindfulness programs and counseling services, may play a strategic role in supporting students’ transition from moderate mental well-being toward flourishing. Novelty/Originality of this study: This study provides empirical insight into students’ mental well-being profiles within the Indonesian higher education context and offers practical implications for the development of guidance and counseling services.